IMPLEMENTATION OF REGIONAL REGULATION CENTRAL JAVA PROVINCE NO.11 OF 2014 ON THE FULFILLMENT OF RIGHTS PEOPLE WITH DISABILITIES IN 5 JUNIOR HIGH SCHOOL SEMARANG - rianto, Anisah Dewi; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Fulfillment of the rights of people with disabilities is all activities to fulfil the obligations and protect people with disabilities and their rights so they can live, grow, develop and participate optimally according to standard and human dignity and get protection from violence and discrimination. This research focused on education sector by the existence of inclusive schools and implementation in 5 Junior High School State as the one of the inclusive schools in the city of Semarang. This study aims to analyse the process of implementation the policy of fulfilling the rights of people with disabilities on the education sector in 5 Junior High School State and analyze the factors that influence the success of the policy. This research used qualitative descriptive research methods conducted through interviews with several selected informants using purposive sampling technique. The result of the study shows the implementation of the policy of fulfilling the rights of people with disabilities in education sector in 5 Junior High School State Semarang has not been optimally influenced by the ability of subject teachers who are still not optimal in handling Children with Special Needs in class, as well as inter-organizational communication in the form of optimal coordination and clarity of information from the school. The recommended advice is to present of technical guidance for teachers in schools, increasing the process of coordination and providing clarity of information from education officer to the school in determining the target schools for persons with disabilities.